Impact of endostatin gene therapy on myeloid-derived suppressor cells from a metastatic renal cell carcinoma - Chaves, K.C.B.; Costa, E.M.; Teixeira, L.F.; Bellini, M.H. (Experimental Oncology, 2018)
Aim: To evaluate the role of endostatin (ES) gene therapy on myeloid-derived suppressor cells (MDSC) in a metastatic model of renal cell carcinoma (RCC). Materials and Methods: Balb/C mice bearing orthotopic Renca tumors were treated with NIH/3T3LendSN or, as a control, with NIH/3T3-LXSN cells. At the end of in vivo experiment, plasma and tissue lung samples were collected. Plasma ES and granulocyte colony stimulating factor (G-CSF) levels were measured by ELISA and Milliplex, respectively. Quantification of CD11b⁺Gr⁻1⁺ cells and their subsets was performed by flow cytometry. Reactive oxygen species (ROS) production was measured in CD11b⁺Gr⁻1⁺ MDSC using the DCFDA marker by flow cytometry. Results: Metastatic RCC (mRCC) induced expansions of CD11b⁺Gr⁻1⁺ MDSC and promoted accumulation of these cells and their subtypes in lymphoid organ and metastases. ES treatment promoted low G-CSF plasmatic levels which were produced by the tumor microenvironment, reflecting the reduced metastatic accumulation of CD11b⁺Gr⁻1⁺ MDSC in the lungs. However, the therapy was selective for granulocytic cells, thus reducing the production of ROS. Conclusion: These findings confirm the expansion of MDSC during metastatic progression of RCC and indicate the important role of ES in reducing MDSC and possible use of ES therapy in combined anticancer treatment.